U.S. corporate governance - Chew, Donald H.; Gillan, Stuart L. (Columbia Business School Publishing, 2009)
Corporate governance constitutes the internal and external institutions, markets, policies, and processes designed to help companies maximize their efficiency and value. In this collection of classic and current articles from the Journal of Applied Corporate Finance, thought leaders such as Michael Jensen and Robert Monks discuss the corporate mission of value maximization and the accomplishments and limitations of U.S. governance in achieving that end.--[book cover].